Transcriptomic/proteomic identification of allergens in the mite Tyrophagus putrescentiae. Issue 11 (25th August 2016) - Cui, Y.; Yu, L.; Teng, F.; Zhang, C.; Wang, N.; Yang, L.; Zhou, Y.
Abstract: While a number of allergens from house dust mites have been described, much remains to be discovered about allergens from storage mites. Here, next‐generation sequencing was combined with MS/MS shotgun proteomics to identify proteins, especially potential allergens from Tyrophagus putrescentiae, commonly found in stored food products, especially flour. cDNAs of suspected allergens were cloned and expressed from bacterial cells, and recombinant allergens were tested for binding to IgE in sera from T. putrescentiae ‐sensitive patients. These analyses identified three previously uncharacterized allergens, Tyr p 28, Tyr p 35, and Tyr p 36, which have been officially assigned by the WHO/IUIS Allergen Nomenclature Sub‐committee. Recombinant proteins rTyr p 28, rTyr p 35, and rTyr p 36 bound with 47.1%, 82.4%, and 70.6% of T. putrescentiae ‐sensitive sera. We provide here a new method to identify allergens by the combination of transcriptomic and proteomic approaches.